Endografts for the treatment of abdominal aortic aneurysms with a hostile neck anatomy: A systematic review - Pitros, Christos; Mansi, Pietro; Kakkos, Stavros (Frontiers in Surgery, 2022)
Background Endovascular aortic repair (EVAR) of abdominal aortic aneurysms (AAAs) has emerged as a better alternative to conventional open surgery for AAAs. The purpose of the review is to define the improvement in the clinical management of the patient with hostile neck AAAs due to the introduction of new endografts while giving a thorough description of their instructions for use (IFUs), main characteristics and part sizing, reporting their outcomes from clinical studies and categorizing their usability. Methods A MEDLINE search was conducted using keyword-specific combinations. Clinical studies were searched via the clinicaltrials.gov website. Relevant articles' references were also hand-searched. Results We retrieved 640 records describing Alto, Ovation iX, Treovance, Aorfix, Anaconda, Conformable, and Endurant II/IIs endografts. Aortic necks >60° can be managed with Anaconda, Aorfix, and Conformable, which can treat up to 90° necks requiring ≥15 mm (Anaconda ≥20 mm), and Treovance, which is eligible for necks ≤75° with ≥15 mm length. Ovation's innovation of combining polymer-filled O-rings with integral anchors can treat conical necked AAAs giving Ovation iX and Alto an advantage. Short-necked AAAs can be treated with Alto, eligible for necks as short as 7 mm, and Endurant II, which can treat ≥10 mm necks or 4 mm if used in conjunction with the EndoAnchors system, respectively. Alto and Conformable report a 100% technical success rate, absence of AAA-related death, migration, ruptures, and limb occlusion during follow-up. Endurant II and Ovation iX report >99% technical success rate and are almost free from the AAA mortality rate, ruptures, migration, and limb occlusion, while Ovation iX has a high rate of sac dilation (15.5%) in a 5-year follow-up. Anaconda is slightly better than Aorfix and Treovance, which are related to the lowest technical success rates, 98.3%, 96.3%, and 96%, respectively. Aorfix has the highest AAA mortality rate, 4% in a 60 month follow-up. Conclusion Most new generation endografts described have comparable results. They broaden the eligibility of patients for EVAR due to their unique technical characteristics described. There is a lack of comparative studies for newer endografts and postmarket clinical studies with long-term results concerning the most recently approved devices described, Alto and Conformable.